Green synthesis of nickel oxide hole transport layer via aloe vera extract-assisted sol-gel process - Islam M.A.; Selvanathan V.; Chelvanathan P.; Haque M.M.; Mottakin M.; Alnaser I.A.; Karim M.R.; Ibrahim M.A.; Suemasu T.; Akhtaruzzaman M. (Springer, 2025)
In perovskite solar cells (PSCs), the instability concern and complex synthesis process of organic hole transport layers (HTL) have led researchers to focus on widely available inorganic NiOx as an effective alternative. Herein, an eco-friendly and cost-effective green synthesis method has been implemented to fabricate the NiOx thin film using aloe vera (AV) leaf extract as a complexing agent and the effect of different calcination temperatures (300 C, 400 C and 500 C) on the film?s properties have been thoroughly studied. XRD analysis has shown improved crystallinity in the films that were calcined at higher temperatures. Both Raman spectroscopy and EDX analysis have revealed the presence of low carbon content in all deposited thin films. The film calcined at 300 C has shown the most favorable morphology that has been confirmed from the FESEM images. The band gap of the films has been shifted from 3.83 eV to 3.73 eV as the calcination temperature increased. Upon electrical characterizations, the film calcined at 500 C has demonstrated the highest hole mobility (20.3 cm/Vs). The results from numerical simulation have indicated that the PSC employing the NiOx HTL calcined at 500 C exhibits the highest PCE, Voc and FF values of 16.04%, 1.70 V and 67.35%, respectively, while the film calcined at 300 C results the highest Jsc (14.95 mA/cm). (Figure presented.). ? The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.